Intake of whole grains is associated with lower risk of myocardial infarction: the Danish Diet, Cancer and Health Cohort. Issue 4 (17th February 2016) - Helnæs, Anne; Kyrø, Cecilie; Andersen, Ingelise; Lacoppidan, Sandra; Overvad, Kim; Christensen, Jane; Tjønneland, Anne; Olsen, Anja
ABSTRACT: Background: High intake of whole grains has been associated with lower risk of coronary heart disease; however, the research that has been used to evaluate different effects of different whole-grain cereals (e.g., wheat, rye, and oats) has been sparse. Objective: We investigated the association between whole-grain intake in terms of total intake and intakes of different cereals and myocardial infarction. Design: This prospective study included 54, 871 Danish adults aged 50–64 y, of whom 2329 individuals developed myocardial infarction (13.6 y of follow-up). Detailed information on daily intake of whole-grain products was available from a self-administered food-frequency questionnaire, and intakes of total whole grain and whole-grain species (wheat, rye, and oats) were estimated. The association between intake of whole grains and risk of myocardial infarction was examined with the use of a Cox proportional hazards model adjusted for potential confounders. Results: For both men and women with total whole-grain intake in the highest quartile, lower risks of myocardial infarction were shown [HRs: 0.75 (95% CI: 0.65, 0.86) and 0.73 (95% CI: 0.58, 0.91), respectively] than for individuals with intake in the lowest quartile. When the specific cereal species were considered, rye and oats, but not wheat, were associated with lower myocardial infarction risk in men. No significant associations were seen in women. For total whole-grain products, significantly lower myocardial infarction risks were seen with higher intakes in both men and women. Rye bread (in men and women) and oatmeal (in men) were associated with significantly lower risk of myocardial infarction, whereas no significant association was shown for whole-grain bread, crispbread, and wheat. Conclusion: In this study, we provide support for the hypothesis that whole-grain intake is related to lower risk of myocardial infarction and suggest that the cereals rye and oats might especially hold a beneficial effect.